Sleep quality in people with chronic pain undergoing hemodialysis - Erika Veríssimo Dias Sousa; Luis Angel Cendejas Medina; Marina Guerra Martins; Carla Regina de Souza Teixeira; Samia Jardelle Costa de Freitas Maniva; Joselany Áfio Caetano (Universidade Federal do Ceará, 2023)
Objective: to evaluate sleep quality in people with chronic pain undergoing hemodialysis. Methods: observational, prospective, and cross-sectional study carried out in two hemodialysis clinics. The sample was formed by 76 people with chronic kidney disease and chronic pain who were undergoing hemodialysis. We used a sociodemopgrahic and clinical form, the visual analogue scale for pain, the McGill questionnaire, and the Pittsburgh Sleep Quality Index. Results were analyzed using descriptive and inferential statistics and correlation tests. Results: most participants had very poor sleep quality. There was a correlation between sleep quality and the visual analogue scale for pain (p=0.027). There was a negative correlation between McGill pain scale descriptors and sleep quality (p=0.033). Conclusion: the sleep quality levels of most participants suffered alterations and were classified as poor or very poor. Contributions to practice: this study provides data on correlations associated with the sleep quality of patients with chronic pain undergoing hemodialysis. It also gives support for nursing teams to develop interventions to improve the sleep quality of these patients.